2021
DOI: 10.1016/j.placenta.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Third trimester stillbirth during the first wave of the SARS-CoV-2 pandemic: Similar rates with increase in placental vasculopathic pathology

Abstract: Whether SARS-CoV-2 definitively increases the risk of stillbirth is unknown, though studies have suggested possible trends of stillbirth increase during the pandemic. This study of third trimester stillbirth does not identify an increase in stillbirth rates during the pandemic period, however investigation of the placental pathology demonstrated trends towards more vascular placental abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…There are mixed findings as to whether maternal SARS-CoV-2 infection leads to an increased risk of poor pregnancy outcomes, particularly stillbirth. Whilst there are reports of an increased risk of stillbirth (18,19), other studies have reported no difference (20,21). There have been reports of an increase in neonatal deaths (7,19); however, in our study, there were no poor pregnancy outcomes, although this is partly by design as women with Active COVID and a poor pregnancy outcome (e.g., a prior fetal death) were not approached to take part in the study.…”
Section: Poor Pregnancy Outcomes and Placental Pathologycontrasting
confidence: 61%
“…There are mixed findings as to whether maternal SARS-CoV-2 infection leads to an increased risk of poor pregnancy outcomes, particularly stillbirth. Whilst there are reports of an increased risk of stillbirth (18,19), other studies have reported no difference (20,21). There have been reports of an increase in neonatal deaths (7,19); however, in our study, there were no poor pregnancy outcomes, although this is partly by design as women with Active COVID and a poor pregnancy outcome (e.g., a prior fetal death) were not approached to take part in the study.…”
Section: Poor Pregnancy Outcomes and Placental Pathologycontrasting
confidence: 61%
“…Dumont (2021) 47 1 1 PFD with ischemic changes and necrosis of the villi, intervillous space with inflammatory cells and histiocytes. Bunnell (2021) 48 12 12 MVM (n = 5), FVM (n = 5). No massive PFD or HI.…”
Section: Placental Histology and Possible Mechanisms Of Stillbirthmentioning
confidence: 99%
“…Table 2 lists key studies reporting placental histopathological findings associated with stillbirth in pregnancies with maternal SARS‐CoV‐2 infection 40–63 .…”
Section: Association Between Covid‐19 and Stillbirthmentioning
confidence: 99%
“…Unlike the examples discussed above in the germline and yolk, cell fusion is the mechanism of syncytium formation in the placenta (reviewed in Gerbaud and Pidoux 2015 ; Soygur and Sati 2016 ). In humans, there are three distinctly localized syncytial layers of trophoblast cells in the placenta, each thought to play an endocrine and immune barrier function (reviewed in Turco and Moffett 2019 ; Roberts et al 2021 ). Trophoblast layers may be some of the most extreme examples of syncytia in nature, with up to 6 × 10^10 nuclei estimated in a human syncytial trophoblast (Simpson et al 1992 ).…”
Section: Distinct Architecture: a Survey Of Tissues With Extra Genomes Across Naturementioning
confidence: 99%